Was the Long March a Dead End? An Exchange on Radicals and the University. - Kazin, Michael; Shenk, Timothy (Dissent (0012-3846))
The article presents an exchange of letters tackling radicals and higher education in the U.S. Topics discussed include the problems facing students and the higher education sector, the civil rights movement led by college freshmen in 1960, improvements in diversifying the higher education system, the significant role of universities in the history of social movements in the U.S., the surge in hypersensitivity on the issues of gender and race in education, and the primary task of leftists in academia.